ACHIEVING GENDER EQUALITY IN EDUCATION IN CIVIL ENGINEERING IN MONTENEGRO - Perazić, Mladen; Pavličić, Nevenka; Knežević, Miloš (Journal of Applied Engineering Science, 2016)
Achieving gender equality in the process of education is a long procedure which resulted in the fact that the level of education of women in Montenegro has long been equated with the level of education of men. Thus, equal gender opportunities in employment should come as a result of such situation. However, data show that women are failing, as much as men, to ensure a successful career. In recent years, the situation in education in civil engineering has been changed for the better, and in this sense the women occupy an appropriate position in this field of economy.